The influence of temperature to the arrival dates of spring migrants - Ivanauskas, Feliksas; Lapinskas, Remigijus; Nedzinskas, Vytautas (Lietuvos matematikos rinkinys, 2002)
We establish that the day when the average temperature of the 20 days before that for the first time in the year reaches +3 degrees centigrade is the best predictor of the arrival date of the tufted duck to the Zuvintas reservation, Lithuania.